Problems of High School Students in Interpersonal Relationships - Thi My Linh, Nguyen; Khanh, Nguyen Cong (VNU Journal of Science: Education Research; Vol 39 No 3, 2023)
The article presents the current situation of problems faced by high school students in interpersonal relationships. The research sample includes 790 students in grades 10, 11 and 12 at 6 high schools in Hanoi. Research results show that the majority of high school students rate themselves as having few problems (difficulties) in interpersonal relationships. The most common interpersonal problems students face are related to lack of social skills, teamwork, and adapting to new (changing) social environments. Students also rarely have interpersonal problems with teachers. The survey results also found a number of factors that significantly affect the expression level of interpersonal problems of students. This result contributes to providing useful information in early recognition of problems in interpersonal relationships, and as a reliable database when developing educational solutions to improve students’ problem solving capacity in the interpersonal interactions.